Customer Experience Management: Analysis of Customer Retention in Restaurants in Anambra State, Nigeria - Nwankwo Cosmas Anayochukwu; Kanyangale MacDonald Isaac (Marketing of Scientific and Research Organizations, 2023)
This study examined the effect of customer experience management (CEM) on customer retention in restaurants in Anambra State, Nigeria. Specifically, the study sought to investigate the influence of affective customer experience, cognitive customer experience, physical customer experience and social-identity customer experience on customer retention in restaurants in Anambra State, Nigeria. The study adopted a survey research method. The study found that affective customer experience, cognitive customer experience, physical customer experience and social-identity customer experiences have a significant effect on customer retention in restaurants in Anambra State, Nigeria. Based on the foregoing, the study concluded that CEM had a significant effect on customer retention in restaurants in Anambra State, Nigeria. The study recommended, amongst others, that management of restaurants should deliberately focus on humanic clues in terms of providing a conducive environment, especially one that is always clean for its customers.